Lattice Boltzmann Method for Simulating the Temperature Jump and Velocity Slip in Microchannels (Communications in Computational Physics, 2007)
The velocity slip and temperature jump in micro-Couette flow are investigated with the lattice Boltzmann method (LBM). A new slip boundary conditionwith the non-equilibrium extrapolation scheme is used in a thermal lattice Boltzmannmodel (TLBM) where double distribution functions are used to simulate the velocityand the temperature fields in order to capture the velocity slip and the temperaturejump of the wall boundary. The simulated velocity and temperature profiles are ingood agreement with the analytic results, which shows the suitability of the presentmodel and the new boundary treatment for describing thermal microflows with viscous heat dissipation.